2018
DOI: 10.1080/00036846.2018.1467554
|View full text |Cite
|
Sign up to set email alerts
|

External shocks, consumption-smoothing and capital mobility in India: evidence from an intertemporal optimization approach

Abstract: We examine the solvency of India's current account (CA) in the post-liberalization period using intertemporal optimization approach to the CA. Using quarterly data ranging from 1996Q1 to 2014Q2, we estimate a benchmark consumption-smoothing model and an extended model that incorporates external shocks. Overall, we find that the predicted optimal CA in both the models can track the actual CA movements and the extended model performs better over the benchmark model. Further, we also find that the optimal CA is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(32 reference statements)
0
3
0
1
Order By: Relevance
“…Source: U.S. Energy Information Administration.2 It is argued that in recent years oil price movements were mainly driven by demand factors rather than supply side disturbances. Furthermore,Garg and Prabheesh (2018) have argued that oilimporting EMEs show greater vulnerability to oil price shocks.…”
mentioning
confidence: 99%
“…Source: U.S. Energy Information Administration.2 It is argued that in recent years oil price movements were mainly driven by demand factors rather than supply side disturbances. Furthermore,Garg and Prabheesh (2018) have argued that oilimporting EMEs show greater vulnerability to oil price shocks.…”
mentioning
confidence: 99%
“…Thus, these agents will always try to smooth their consumption in case of any future random variations in their income. In this case, the smoothing takes place either by borrowing or lending (Garg and Prabheesh, 2018). In other words, if there is a variation in the current income then to maintain a stable consumption level, saving will adjust accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…Landeau (2002) found that the CA balance in Chile is solvent over the period 1960-1999. Similar results were found by Darku (2010) in the case of Ghana over the period 1960-2002. In the case of India, Khundrakpam and Ranjan (2009) utilized a similar model to Callen and Cashin (1999) and Garg and Prabheesh (2018) and found that the solvency condition is met. On the other hand, few studies found that the solvency criterion is violated.…”
Section: Introductionmentioning
confidence: 99%
“…A volatilidade da conta corrente observada comparada à teórica sob perfeita mobilidade de capital seria capaz de indicar o grau de mobilidade internacional do capital. Esta interpretação teórica é discutida na literatura como em Cashin & McDermott (1998), Agénor et al (1999), Hussien & Mello Jr. (1999, Bergin & Sheffrin (2000), Ismail & Baharumshah (2008), Ogus & Sohrabji (2008), Garg & Prabheesh (2018), Singh (2019) entre outros. Huang (2010) assume que flutuações nos termos de troca também podem agir como indutoras do movimento da conta corrente suavizadora, de forma a não as considerar possivelmente levaria a atribuir o movimento da conta corrente a outros fatores, como à mobilidade de capital.…”
Section: Introductionunclassified